The Morphology of Wool Fibers Biodegraded in Natural Conditions in Soil - Monika Rom; Jan Broda; Tomasz Kukulski; Andrzej Gawlowski; Katarzyna Kobiela-Mendrek (Journal of Natural Fibers)
The morphology of sheep wool applied as organic fertilizer biodegraded in the soil was examined. The investigations were conducted in natural conditions for unwashed waste wool, which was rejected during sorting and then chopped into short segments and wool pellets. Different types of wool were mixed with soil and buried in experimental plots. The wool samples were periodically taken and analyzed for one year using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray Spectroscopy (EDS). During examinations, the changes in the fibers’ morphology were observed. It was stated that cut wool and pellet are mechanically damaged, which significantly accelerates wool biodegradation and quickly destroys the whole fiber structure. On the contrary, for undamaged fibers biodegradation occurs slowly, layer by layer, in a predictable sequence. This finding has practical implications for the use of wool as an organic fertilizer, suggesting that the method of preparation can influence its biodegradation rate.